FROM WIDOWHOOD TO LATE-LIFE REPARTNERING: A FEMINIST LENS ON WOMEN IN RELATION TO MEN. (11th November 2018) - Koren, C
Abstract: Late-life repartnering is a possible consequence of widowhood. Based on gender differences, the aim is to compare how older repartnered widows and widowers dealt with widowhood. 27 couples (54 widowed participants), were chosen from two larger studies. One took a dyadic approach (interviewing both partners), and the other an intergenerational perspective (interviewing both partners and offspring). Criterion sampling included widowers and widows who repartned at retirement age or older and who had children and grandchildren from a lifelong marriage that had ended with the death of their spouse. All semi-structured interviews were analyzed based on grounded theory principles and dyadic analysis adapted to families. Findings present a grounded model indicating gender differences in dealing with the death of a lifelong spouse. Men tended to experience vulnerability whereas women tended to experience resilience. Findings are discussed using (critical) feminist gerontology. The innovation being the reversal of gender inequality in old age.